Rise and Thrive with Science: Teaching PK-5 Science and Engineering - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Research shows that that children learn science and engineering subjects best by engaging from an early age in the kinds of practices used by real scientists and engineers. By doing science and engineering, children not only develop and refine their understanding of the core ideas and crosscutting concepts of these disciplines, but can also be empowered to use their growing understanding to make sense of questions and problems relevant to them. This approach can make learning more meaningful, equitable, and lasting. Using cases and shorter examples, Rise and Thrive with Science shows what high-quality teaching and learning in science and engineering can look like for preschool and elementary school children. Through analyses of these examples and summaries of research findings, the guide points out the key elements of a coherent, research-grounded approach to teaching and learning in science and engineering. This guide also discusses the kinds of support that educators need to implement effective and equitable instruction for all children. This book will provide inspiration for practitioners at the preschool and elementary levels to try new strategies for science and engineering education, whatever their level of experience. Rise and Thrive with Science will be an essential guide for teachers as they organize instruction to enable young children to carry out their own science investigations and engineering design projects, determine the kinds of instruction that lead to meaningful learning, and try to engage every one of their students.
Keywords: Education

Call to Action for Science Education: Building Opportunity for the Future - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Scientific thinking and understanding are essential for all people navigating the world, not just for scientists and other science, technology, engineering and mathematics (STEM) professionals. Knowledge of science and the practice of scientific thinking are essential components of a fully functioning democracy. Science is also crucial for the future STEM workforce and the pursuit of living wage jobs. Yet, science education is not the national priority it needs to be, and states and local communities are not yet delivering high quality, rigorous learning experiences in equal measure to all students from elementary school through higher education. Call to Action for Science Education: Building Opportunity for the Future articulates a vision for high quality science education, describes the gaps in opportunity that currently exist for many students, and outlines key priorities that need to be addressed in order to advance better, more equitable science education across grades K-16. This report makes recommendations for state and federal policy makers on ways to support equitable, productive pathways for all students to thrive and have opportunities to pursue careers that build on scientific skills and concepts. Call to Action for Science Education challenges the policy-making community at state and federal levels to acknowledge the importance of science, make science education a core national priority, and empower and give local communities the resources they must have to deliver a better, more equitable science education.
Keywords: Education

Teaching K-12 Science and Engineering During a Crisis - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The COVID-19 pandemic is resulting in widespread and ongoing changes to how the K-12 education system functions, including disruptions to science teaching and learning environments. Students and teachers are all figuring out how to do schooling differently, and districts and states are working overtime to reimagine systems and processes. This is difficult and stressful work in the middle of the already stressful and sometimes traumatic backdrop of the global pandemic. In addition, students with disabilities, students of color, immigrants, English learners, and students from under-resourced communities have been disproportionately affected, both by the pandemic itself and by the resulting instructional shifts. Teaching K-12 Science and Engineering During a Crisis aims to describe what high quality science and engineering education can look like in a time of great uncertainty and to support practitioners as they work toward their goals. This book includes guidance for science and engineering practitioners - with an emphasis on the needs of district science supervisors, curriculum leads, and instructional coaches. Teaching K-12 Science and Engineering During a Crisis will help K-12 science and engineering teachers adapt learning experiences as needed to support students and their families dealing with ongoing changes to instructional and home environments and at the same time provide high quality in those experiences.
Keywords: Education

The Mathematical Sciences in 2025 - National Research Council (The National Academies Press, 2013)
The mathematical sciences are part of nearly all aspects of everyday life—the discipline has underpinned such beneficial modern capabilities as Internet search, medical imaging, computer animation, numerical weather predictions, and all types of digital communications. The Mathematical Sciences in 2025 examines the current state of the mathematical sciences and explores the changes needed for the discipline to be in a strong position and able to maximize its contribution to the nation in 2025. It finds the vitality of the discipline excellent and that it contributes in expanding ways to most areas of science and engineering, as well as to the nation as a whole, and recommends that training for future generations of mathematical scientists should be re-assessed in light of the increasingly cross-disciplinary nature of the mathematical sciences. In addition, because of the valuable interplay between ideas and people from all parts of the mathematical sciences, the report emphasizes that universities and the government need to continue to invest in the full spectrum of the mathematical sciences in order for the whole enterprise to continue to flourish long-term.
Keywords: Math, Chemistry, and Physics; Education; Surveys and Statistics

Next Generation Science Standards: For States, By States (The National Academies Press, 2013)
Next Generation Science Standards identifies the science all K-12 students should know. These new standards are based on the National Research Council's A Framework for K-12 Science Education. The National Research Council, the National Science Teachers Association, the American Association for the Advancement of Science, and Achieve have partnered to create standards through a collaborative state-led process. The standards are rich in content and practice and arranged in a coherent manner across disciplines and grades to provide all students an internationally benchmarked science education. The print version of Next Generation Science Standards complements the nextgenscience.org website and:
Keywords: Education

Surrounded by Science: Learning Science in Informal Environments - National Research Council (The National Academies Press, 2010)
Practitioners in informal science settings—museums, after-school programs, science and technology centers, media enterprises, libraries, aquariums, zoos, and botanical gardens—are interested in finding out what learning looks like, how to measure it, and what they can do to ensure that people of all ages, from different backgrounds and cultures, have a positive learning experience.
Keywords: Education

Science and Engineering for Grades 6-12: Investigation and Design at the Center - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
It is essential for today's students to learn about science and engineering in order to make sense of the world around them and participate as informed members of a democratic society. The skills and ways of thinking that are developed and honed through engaging in scientific and engineering endeavors can be used to engage with evidence in making personal decisions, to participate responsibly in civic life, and to improve and maintain the health of the environment, as well as to prepare for careers that use science and technology.
Keywords: Education

Expanding Underrepresented Minority Participation: America's Science and Technology Talent at the Crossroads - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2011)
In order for the United States to maintain the global leadership and competitiveness in science and technology that are critical to achieving national goals, we must invest in research, encourage innovation, and grow a strong and talented science and technology workforce. Expanding Underrepresented Minority Participation explores the role of diversity in the science, technology, engineering and mathematics (STEM) workforce and its value in keeping America innovative and competitive. According to the book, the U.S. labor market is projected to grow faster in science and engineering than in any other sector in the coming years, making minority participation in STEM education at all levels a national priority. Expanding Underrepresented Minority Participation analyzes the rate of change and the challenges the nation currently faces in developing a strong and diverse workforce. Although minorities are the fastest growing segment of the population, they are underrepresented in the fields of science and engineering. Historically, there has been a strong connection between increasing educational attainment in the United States and the growth in and global leadership of the economy. Expanding Underrepresented Minority Participation suggests that the federal government, industry, and post-secondary institutions work collaboratively with K-12 schools and school systems to increase minority access to and demand for post-secondary STEM education and technical training. The book also identifies best practices and offers a comprehensive road map for increasing involvement of underrepresented minorities and improving the quality of their education. It offers recommendations that focus on academic and social support, institutional roles, teacher preparation, affordability and program development.
Keywords: Education; Policy for Science and Technology; Engineering and Technology; Math, Chemistry, and Physics; Industry and Labor

Seeing Students Learn Science: Integrating Assessment and Instruction in the Classroom - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Science educators in the United States are adapting to a new vision of how students learn science. Children are natural explorers and their observations and intuitions about the world around them are the foundation for science learning. Unfortunately, the way science has been taught in the United States has not always taken advantage of those attributes. Some students who successfully complete their K–12 science classes have not really had the chance to "do" science for themselves in ways that harness their natural curiosity and understanding of the world around them.
Keywords: Education

Science and Engineering in Preschool Through Elementary Grades: The Brilliance of Children and the Strengths of Educators - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Starting in early childhood, children are capable of learning sophisticated science and engineering concepts and engage in disciplinary practices. They are deeply curious about the world around them and eager to investigate the many questions they have about their environment. Educators can develop learning environments that support the development and demonstration of proficiencies in science and engineering, including making connections across the contexts of learning, which can help children see their ideas, interests, and practices as meaningful not just for school, but also in their lives. Unfortunately, in many preschool and elementary schools science gets relatively little attention compared to English language arts and mathematics. In addition, many early childhood and elementary teachers do not have extensive grounding in science and engineering content. Science and Engineering in Preschool through Elementary Grades provides evidence-based guidance on effective approaches to preschool through elementary science and engineering instruction that supports the success of all students. This report evaluates the state of the evidence on learning experiences prior to school; promising instructional approaches and what is needed for implementation to include teacher professional development, curriculum, and instructional materials; and the policies and practices at all levels that constrain or facilitate efforts to enhance preschool through elementary science and engineering. Building a solid foundation in science and engineering in the elementary grades sets the stage for later success, both by sustaining and enhancing students' natural enthusiasm for science and engineering and by establishing the knowledge and skills they need to approach the more challenging topics introduced in later grades. Through evidence-based guidance on effective approaches to preschool through elementary science and engineering instruction, this report will help teachers to support the success of all students.
Keywords: Education

Taking Science to School: Learning and Teaching Science in Grades K-8 - National Research Council (The National Academies Press, 2007)
What is science for a child? How do children learn about science and how to do science? Drawing on a vast array of work from neuroscience to classroom observation, Taking Science to School provides a comprehensive picture of what we know about teaching and learning science from kindergarten through eighth grade. By looking at a broad range of questions, this book provides a basic foundation for guiding science teaching and supporting students in their learning. Taking Science to School answers such questions as:
Keywords: Education

Ready, Set, SCIENCE!: Putting Research to Work in K-8 Science Classrooms - National Research Council (The National Academies Press, 2008)
What types of instructional experiences help K-8 students learn science with understanding? What do science educators, teachers, teacher leaders, science specialists, professional development staff, curriculum designers, and school administrators need to know to create and support such experiences? Ready, Set, Science! guides the way with an account of the groundbreaking and comprehensive synthesis of research into teaching and learning science in kindergarten through eighth grade. Based on the recently released National Research Council report Taking Science to School: Learning and Teaching Science in Grades K-8, this book summarizes a rich body of findings from the learning sciences and builds detailed cases of science educators at work to make the implications of research clear, accessible, and stimulating for a broad range of science educators. Ready, Set, Science! is filled with classroom case studies that bring to life the research findings and help readers to replicate success. Most of these stories are based on real classroom experiences that illustrate the complexities that teachers grapple with every day. They show how teachers work to select and design rigorous and engaging instructional tasks, manage classrooms, orchestrate productive discussions with culturally and linguistically diverse groups of students, and help students make their thinking visible using a variety of representational tools. This book will be an essential resource for science education practitioners and contains information that will be extremely useful to everyone ï¿½including parents ï¿½directly or indirectly involved in the teaching of science.
Keywords: Education

A Framework for K-12 Science Education: Practices, Crosscutting Concepts, and Core Ideas - National Research Council (The National Academies Press, 2012)
Science, engineering, and technology permeate nearly every facet of modern life and hold the key to solving many of humanity's most pressing current and future challenges. The United States' position in the global economy is declining, in part because U.S. workers lack fundamental knowledge in these fields. To address the critical issues of U.S. competitiveness and to better prepare the workforce, A Framework for K-12 Science Education proposes a new approach to K-12 science education that will capture students' interest and provide them with the necessary foundational knowledge in the field.
Keywords: Education

Learning Science in Informal Environments: People, Places, and Pursuits - National Research Council (The National Academies Press, 2009)
Informal science is a burgeoning field that operates across a broad range of venues and envisages learning outcomes for individuals, schools, families, and society. The evidence base that describes informal science, its promise, and effects is informed by a range of disciplines and perspectives, including field-based research, visitor studies, and psychological and anthropological studies of learning.
Keywords: Education

Successful K-12 STEM Education: Identifying Effective Approaches in Science, Technology, Engineering, and Mathematics - National Research Council (The National Academies Press, 2011)
Science, technology, engineering, and mathematics (STEM) are cultural achievements that reflect our humanity, power our economy, and constitute fundamental aspects of our lives as citizens, consumers, parents, and members of the workforce. Providing all students with access to quality education in the STEM disciplines is important to our nation's competitiveness. However, it is challenging to identify the most successful schools and approaches in the STEM disciplines because success is defined in many ways and can occur in many different types of schools and settings. In addition, it is difficult to determine whether the success of a school's students is caused by actions the school takes or simply related to the population of students in the school. Successful K-12 STEM Education defines a framework for understanding "success" in K-12 STEM education. The book focuses its analysis on the science and mathematics parts of STEM and outlines criteria for identifying effective STEM schools and programs. Because a school's success should be defined by and measured relative to its goals, the book identifies three important goals that share certain elements, including learning STEM content and practices, developing positive dispositions toward STEM, and preparing students to be lifelong learners. A successful STEM program would increase the number of students who ultimately pursue advanced degrees and careers in STEM fields, enhance the STEM-capable workforce, and boost STEM literacy for all students. It is also critical to broaden the participation of women and minorities in STEM fields. Successful K-12 STEM Education examines the vast landscape of K-12 STEM education by considering different school models, highlighting research on effective STEM education practices, and identifying some conditions that promote and limit school- and student-level success in STEM. The book also looks at where further work is needed to develop appropriate data sources. The book will serve as a guide to policy makers; decision makers at the school and district levels; local, state, and federal government agencies; curriculum developers; educators; and parent and education advocacy groups.
Keywords: Education; Engineering and Technology

Reopening K-12 Schools During the COVID-19 Pandemic: Prioritizing Health, Equity, and Communities - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The COVID-19 pandemic has presented unprecedented challenges to the nation's K-12 education system. The rush to slow the spread of the virus led to closures of schools across the country, with little time to ensure continuity of instruction or to create a framework for deciding when and how to reopen schools. States, districts, and schools are now grappling with the complex and high-stakes questions of whether to reopen school buildings and how to operate them safely if they do reopen. These decisions need to be informed by the most up-to-date evidence about the SARS-CoV-2 virus that causes COVID-19; about the impacts of school closures on students and families; and about the complexities of operating school buildings as the pandemic persists. Reopening K-12 Schools During the COVID-19 Pandemic: Prioritizing Health, Equity, and Communities provides guidance on the reopening and operation of elementary and secondary schools for the 2020-2021 school year. The recommendations of this report are designed to help districts and schools successfully navigate the complex decisions around reopening school buildings, keeping them open, and operating them safely.
Keywords: Education; Health and Medicine

Cultivating Interest and Competencies in Computing: Authentic Experiences and Design Factors - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Computing in some form touches nearly every aspect of day to day life and is reflected in the ubiquitous use of cell phones, the expansion of automation into many industries, and the vast amounts of data that are routinely gathered about people's health, education, and buying habits. Computing is now a part of nearly every occupation, not only those in the technology industry. Given the ubiquity of computing in both personal and professional life, there are increasing calls for all learners to participate in learning experiences related to computing including more formal experiences offered in schools, opportunities in youth development programs and after-school clubs, or self-initiated hands-on experiences at home. At the same time, the lack of diversity in the computing workforce and in programs that engage learners in computing is well-documented. It is important to consider how to increase access and design experiences for a wide range of learners. Authentic experiences in STEM - that is, experiences that reflect professional practice and also connect learners to real-world problems that they care about - are one possible approach for reaching a broader range of learners. These experiences can be designed for learners of all ages and implemented in a wide range of settings. However, the role they play in developing youths' interests, capacities, and productive learning identities for computing is unclear. There is a need to better understand the role of authentic STEM experiences in supporting the development of interests, competencies, and skills related to computing. Cultivating Interest and Competencies in Computing examines the evidence on learning and teaching using authentic, open-ended pedagogical approaches and learning experiences for children and youth in grades K-12 in both formal and informal settings. This report gives particular attention to approaches and experiences that promote the success of children and youth from groups that are typically underrepresented in computing fields. Cultivating Interest and Competencies in Computing provides guidance for educators and facilitators, program designers, and other key stakeholders on how to support learners as they engage in authentic learning experiences.
Keywords: Education; Computers and Information Technology

Monitoring Progress Toward Successful K-12 STEM Education: A Nation Advancing? - National Research Council (The National Academies Press, 2013)
Following a 2011 report by the National Research Council (NRC) on successful K-12 education in science, technology, engineering, and mathematics (STEM), Congress asked the National Science Foundation to identify methods for tracking progress toward the report's recommendations. In response, the NRC convened the Committee on an Evaluation Framework for Successful K-12 STEM Education to take on this assignment. The committee developed 14 indicators linked to the 2011 report's recommendations. By providing a focused set of key indicators related to students' access to quality learning, educator's capacity, and policy and funding initiatives in STEM, the committee addresses the need for research and data that can be used to monitor progress in K-12 STEM education and make informed decisions about improving it.
Keywords: Education; Behavioral and Social Sciences; Surveys and Statistics

English Learners in STEM Subjects: Transforming Classrooms, Schools, and Lives - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The imperative that all students, including English learners (ELs), achieve high academic standards and have opportunities to participate in science, technology, engineering, and mathematics (STEM) learning has become even more urgent and complex given shifts in science and mathematics standards. As a group, these students are underrepresented in STEM fields in college and in the workforce at a time when the demand for workers and professionals in STEM fields is unmet and increasing. However, English learners bring a wealth of resources to STEM learning, including knowledge and interest in STEM-related content that is born out of their experiences in their homes and communities, home languages, variation in discourse practices, and, in some cases, experiences with schooling in other countries.
Keywords: Education

Identifying and Supporting Productive STEM Programs in Out-of-School Settings - National Research Council (The National Academies Press, 2015)
More and more young people are learning about science, technology, engineering, and mathematics (STEM) in a wide variety of afterschool, summer, and informal programs. At the same time, there has been increasing awareness of the value of such programs in sparking, sustaining, and extending interest in and understanding of STEM. To help policy makers, funders and education leaders in both school and out-of-school settings make informed decisions about how to best leverage the educational and learning resources in their community, this report identifies features of productive STEM programs in out-of-school settings. Identifying and Supporting Productive STEM Programs in Out-of-School Settings draws from a wide range of research traditions to illustrate that interest in STEM and deep STEM learning develop across time and settings. The report provides guidance on how to evaluate and sustain programs. This report is a resource for local, state, and federal policy makers seeking to broaden access to multiple, high-quality STEM learning opportunities in their community.
Keywords: Education